Virtual Laboratories for Learning Chemistry and Physics Through Chemlab and Modellus - Alulima Alulima, Lidya (2023)
In the present-day context, educational institutions have difficulties maintaining technological equipment available to the academic community. Therefore, the technology tools’ implementation for teaching Physics and Chemistry, through virtual laboratories in applications such as Chemlab and Modellus, is pertinent. The objective is to analyze Chemlab and Modellus simulators as didactic strategies that allow integral learning between theory and practice, applied to 200 high-school students of a public educational institution. The methodology is based on a mixed approach to gather information followed by an analysis and interpretation of the results, which are relevant to the use of qualitative and quantitative data based on the measurement of the variables. The subsequent results show satisfaction in the processes according to a survey of professional experts in the area and students who demonstrate to be satisfied acquiring and understanding contents and topics related to the environment reducing the difficulty degree, awakening interest, achieving a balance between theoretical concepts with experimentation and solving exercises, consolidating acquired competencies such as communication and technological skills, critical thinking, autonomy, collaborative work, leadership, decision-making, and resolution capacity.